Reexamining the link between parental knowledge and delinquency: unpacking the influence of adolescents' and their parents' perceptions. Issue 6 (3rd June 2019) - Scheuerman, Heather L.; Grosholz, Jessica M.; Thaxton, Sherod
ABSTRACT: Parents' and their children's perceptions of how much parents know about the child's activities outside parental presence (parental knowledge) are important for understanding delinquency. Yet, conceptual and methodological deficiencies in prior research may limit this understanding. Reexamining how these perceptions affect delinquency, we find that contrary to conventional wisdom: (1) adolescent and parent perceptions of parental knowledge impact delinquency jointly rather than independently and (2) the protective effect of adolescent perceptions weakens as parent perceptions increase. Specifically, when parental perceptions are strongest, the delinquency inhibiting effect of adolescent perceptions is offset, which may result from stress of parents' monitoring efforts.